A comprehensive microbiome analysis of wheat and its wild relatives - Cantor, Heather, author; Byrne, Patrick F., advisor; Broders, Kirk, committee member; Stromberger, Mary, committee member (Colorado State University. Libraries, 2018)
Microbiomes are diverse assemblages of endophytic and free-living microorganisms that can confer competitive advantages to their plant hosts such as water acquisition, nutrient mobilization, drought tolerance, salt tolerance, and disease resistance (Chaparro et al., 2012; Sherameti et al., 2008; Zolla et al., 2013). Plant domestication and selective breeding have altered the composition of these plant-microbe interactions in several crops. It is thought that the progenitors of the A, B, and D genomes in modern hexaploid wheat (Triticum aestivum) manage environmental stress in their native environment by establishing symbioses with a consortium of beneficial microbes (Iannucci et al., 2017). However, these microbial communities are not well understood. The goal of this study is to better understand the core community of microbes in wild wheat relatives and how they differ from the microbiome of cultivated wheat. This study compares the bacterial and fungal taxa found in and on the leaves, roots, and rhizosphere of three accessions of hard winter wheat and 14 accessions of eight wild relative species grown in a common soil. These plants and the agricultural soil they inhabit were sampled from a randomized complete block design with two replications, grown in well-watered and water-limited treatments in Fort Collins, Colorado. DNA was extracted and barcoded amplicon sequencing of the 16S-V4 (bacteria/archaea) and ITS2 (fungi) small subunit ribosomal RNA (rRNA) genes was used to describe the diversity of the microbial community associated with the root, rhizosphere and leaves of each accession. The results indicate that while there were limited differences in microbial communities among plant species, plant tissue type appears to be a strong predictor of microbial community structure. Across all plant genotypes, the rhizosphere consistently contained the most diverse and abundant microbiomes, followed by roots, and lastly leaves, which were the least diverse tissue type. When these three tissue types were analyzed independently (PERMANOVA), there was a significant difference in rhizosphere communities between the wet and dry treatments. Wet treatments contained a greater number of facultative anaerobes and bacteria common to cold, saturated soils. The wet treatment received an additional 13 mm of water, applied five days prior to collection. Overall, while plant host genotypes did not differ significantly in their microbiomes, some unique symbioses among different plant accessions indicate evolutionary adaptation. An initial look at the core microbiome shared among representatives of the five plant genomes in this study showed few shared sequence variants (<2% of total microbial SV's). However, this was largely explained by the use of high-resolution SV's that do not necessarily equate to different taxonomic assignment, suggesting an inflated number of actual microbial taxa. Coarser taxonomic overviews depicted a more realistic, and narrow, number of participating taxonomic groups in the phytobiome. Plant tissue type remained a chief driver of microbiome composition. Soil moisture and fertility may have also played a role in determining microbial community structure, but since they were not measured in this study, claims cannot as yet be made. The close genetic relationships among plant species in this study may have reduced the observable differences in microbial community structure. Additionally, common garden experiments limit the pool of potential plant-microbe interactions. Despite the advancement and evolution of modern wheat, the microbiome remains essentially the same as the microbiomes of wild relatives, when grown in the same soil. This indicates that modern winter wheat retains the same ability to recruit and sustain its microbiome as its wild relatives. In the future, microbiome consensus studies in these hosts' centers of origin could broaden our understanding of long-evolved microbial symbioses.
Keywords: phytobiome; rhizosphere; wild relatives; plant breeding; microbiome; wheat